Komparasi Metode Simple Addtive Weighting dan Weight Product Menggunakan Sistem Pendukung Keputusan pada Penerimaan BLT - Muhammad Rizky Hamdan; Agung Triayudi; Agus Iskandar (JURIKOM (Jurnal Riset Komputer), 2022)
Direct cash assistance is a program of local government efforts to deal with problems that occur in underprivileged families. This program is sought so that the community has less impact on economic growth and welfare. The methode used this system is.the.Simple Addtive Weighting (SAW) and Weight Product (WP) methods. Simple Additive Weighting (SAW) is a decision making process which in the process adds up the weights of the performance appraisal on all alternative attributes. While the Weight Product (WP) method is an analyst decision.methode for a multi-criteria decision making (MCDM) or multi - criteria decision making (MCDM). The existence of a comparison between the two methods is expected to help better select residents in receiving BLT so that they are more targeted. In this study resulted in a system to determine the citizens who are entitled to receive BLT, based on the result the study. Comparison of the SAW and WP methods using 20 alternative data, shows that the second method gets accurate data and is suitable if applied as a ranking of citizens in BLT receipts. In the ranking occupied by Burhan by getting the highest score on the 2 methods, there is an equal ranking of the 2 methods caused by the alternative performance scores, and the weight value of the first criterion in each method. Results Based on the research, is it recommended to use the SAW method to determine the ranking, cause the Ievel of suitability of.the.data in the field is higher than the WP found 99.40 WP found 99.20%.